2021
DOI: 10.1111/coa.13854
|View full text |Cite
|
Sign up to set email alerts
|

One year into the COVID‐19 pandemic: What do we know so far from studies assessing risk and mitigation of droplet aerosolisation during endonasal surgery? A systematic review

Abstract: March 2020 marked both the first national lockdown in the United Kingdom and the declaration of a global pandemic by the World Health Organisation. As we pass the unhappy anniversary of this time, it invites us to reflect upon the inescapable changes that coronavirus has wrought upon ENT practice. A series of measures were put in place to prevent health services being overwhelmed by COVID-19, initially involving the cancellation of elective surgery across the country. While this primarily aimed to allow reallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Several authors have sought to characterize this risk during endonasal instrumentation. 25 , 26 , 27 , 28 Workman and colleagues found that the use of high-speed drills and bipolar electrocautery generated significant airborne particulates while hand instrumentation and microdebriders with inbuilt suction capacity did not. 25 In contrast, Sharma et.…”
Section: Decreasing Viral Transmission Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have sought to characterize this risk during endonasal instrumentation. 25 , 26 , 27 , 28 Workman and colleagues found that the use of high-speed drills and bipolar electrocautery generated significant airborne particulates while hand instrumentation and microdebriders with inbuilt suction capacity did not. 25 In contrast, Sharma et.…”
Section: Decreasing Viral Transmission Riskmentioning
confidence: 99%
“… 32 Furthermore, risk mitigation strategies include preoperative patient testing. 28 Given the potential for false negative tests from nasopharyngeal swabs and other methods for SARS-CoV-2 testing, several institutions test twice for patients preoperatively and recommend adopting certain safety techniques universally for both SARS-CoV-2 positive and negative patients. 33 , 34 Several studies have evaluated staff SARS-CoV-2 infections in the postoperative setting.…”
Section: Decreasing Viral Transmission Riskmentioning
confidence: 99%